The activity profile of elite male amateur boxing - Davis, P.; Benson, P. R.; Pitty, J. D.; Connorton, A. J.; Waldock, R. (International Journal of Sports Physiology and Performance, 2015)
An activity profile of competitive 3 × 3-min elite-level amateur boxing was created from video footage of 29 Olympic final and semifinal bouts in 39 male boxers (mean ± SD) age 25.1 ± 3.6 y, height 178.3 ± 10.4 cm, and body mass 69.7 ± 16.5 kg. Boxing at this level requires the ability to maintain an activity rate of ~1.4 actions/s, consisting of ~20 punches, ~2.5 defensive movements, and ~47 vertical hip movements, all per minute, over 3 subsequent rounds lasting ~200 s each. Winners had higher total punches landed (P = .041) and a lower ratio of punches thrown to landed (P = .027) than losers in round 3. The hook rearhand landed was also higher for winners than losers in round 2 (P = .038) and round 3 (P = .016), and defensive movements were used less by winners (P = .036). However, the results suggest that technical discrimination between winners and losers is difficult; bout outcome may be more dependent on which punch is "lucky" enough to be scored by the judges or who appears to be dominant on the day. This study gives both boxers and coaches a good idea of where subelite boxers need to aim if they want to become among the best amateur boxers in the world.